2020
DOI: 10.3390/medicina56110579
|View full text |Cite
|
Sign up to set email alerts
|

The Level of Free Fetal DNA as Precise Noninvasive Marker for Chromosomal Aneuploidies: First Results from BALTIC Region

Abstract: Background and objectives: Noninvasive prenatal testing (NIPT), which has been introduced clinically since 2011, uses the circulating cell-free fetal DNA in the maternal blood to evaluate the risk of a chromosomal anomaly. The aim of this study was to examine the effectiveness of NIPT using a single nucleotide polymorphism method. Materials and Methods: A retrospective study was conducted between 2013 and 2019. The Natera Panorama test was used to analyze the risk of trisomies 21, 18, 13, X monosomy, trisomy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Of the total studies included, 8 reported the relationship between fetal gender and the fetal fraction ( 20 23 , 28 , 33 , 37 , 40 ) and 3 studies reported that the fetal fraction in female fetuses is significantly higher than in male fetuses ( 20 , 23 , 28 ). However, 5 studies showed there was no significant association between fetal gender and FF ( 21 , 22 , 33 , 37 , 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the total studies included, 8 reported the relationship between fetal gender and the fetal fraction ( 20 23 , 28 , 33 , 37 , 40 ) and 3 studies reported that the fetal fraction in female fetuses is significantly higher than in male fetuses ( 20 , 23 , 28 ). However, 5 studies showed there was no significant association between fetal gender and FF ( 21 , 22 , 33 , 37 , 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…We can see that most of them were published in 2021 (13 out of 51 studies), likely due to the relatively young age of the investigation technique. Regarding the reviewed studies, 13 are described in the first section concerning the role of cffDNA in the non-invasive prenatal diagnosis of aneuploidies [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], 7 are described in the second section (CNV diseases) and the remaining 31 are in the third section concerning diseases with monogenic transmission [ 2 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…This indicates how improved conditional screening protocols could lead to less use of invasive techniques. A 2020 cohort study by Serapinas et al [ 6 ] reported that NIPT (performed by a single nucleotide polymorphism method) achieved a high positive-predictive value (PPV) for both trisomy 21 and 18. Such a finding confirms the possible use of this test as a definitive diagnostic tool, certainly with regard to trisomy 21.…”
Section: Resultsmentioning
confidence: 99%
“…In comparing the performance of different NIPS platforms for the common trisomies, the SNP-based method has a higher detection rate and lower false positive rate than massively parallel shotgun sequencing [56]. While NIPS is considered to have a high positive predictive value (PPV) for the detection of trisomy 21 or trisomy 18 in singleton pregnancies (99%, 97.7%, respectively) [57], the detection rate for 47,XXY is lower (93%) [58]. Invasive confirmation testing is still recommended to rule out a false positive.…”
Section: Discussionmentioning
confidence: 99%